Effectiveness of Project-Based Learning in Enhancing Mathematical Reasoning and Creativity: A Systematic Review - Dahal, Prem Prasad; G.C., Laxmi (KMC Journal, 2026)
This systematic review incorporates empirical evidence about the effectiveness of Project-Based Learning (PBL) in developing the mathematical reasoning and creativity of students. Following PRISMA 2020 guidelines, twenty peer-reviewed empirical studies conducted on various educational levels and in different international contexts were identified and analyzed. Overall, findings across the included studies are largely in agreement in finding that PBL is related to positive effects on mathematical reasoning and creative thinking compared with more conventional teaching approaches, especially if projects are authentic and interdisciplinary and are supported with structured collaboration. PBL models combined with STEM learning, computational thinking or guided peer interaction (e.g. Think-Pair-Share) tend to report better outcomes. Greater flexibility, fluency, and originality in problem solving and deeper conceptual understanding and reflective reasoning are often exhibited by learners in real-world project tasks. Evidence from a meta-analytic synthesis also indicates a large positive effect of STEM-oriented PBL on creativity also suggesting that interdisciplinary PBL design may enhance creative outcomes. However, the generalizability of results is limited because of the short intervention periods, small sample sizes and the lack of consistency in assessment tools. The review concludes that well-conceived PBL - the provision of a solid foundation in inquiry, authenticity, and formative feedback - can be used to support the development of mathematical reasoning and creativity, while future research should focus on longitudinal and multi-site studies to consider the issue of sustainability in different contexts.